500 Hz ultraviolet dye laser with pulse energy 1.7 mJ and potential for PLIF imaging. Issue 4 (23rd February 2020) - Zhou, Zhigang; Chen, Deying; Fan, Rongwei; Li, Xudong; Chen, Zhaodong; Luo, Tong; Dong, Zhiwei; Jiang, Yugang
ABSTRACT: This paper describes a high-pulse-energy frequency-doubled ultraviolet dye laser operating at a repetition rate of 500 Hz. The pump source is a laser-diode side-pumped Q-switched Nd:YAG laser with a pulse energy of 29 mJ at 532 nm. A master oscillator power amplifier is employed to amplify the output pulse of the dye laser to 8.1 mJ at 566 nm, and by frequency doubling with BBO crystal a pulse energy of 1.7 mJ at 283 nm is achieved with a pulse width of 8 ns. This is more than four times the largest reported pulse energies generated by other fixed-frequency dye lasers when operating at repetition rates of more than 1 kHz. The conversion efficiency and stability of dye laser are discussed, which show the potential for high-speed laser diagnostics in the fields of combustion and turbulent flow detection.